A influência exercida pelo sistema de avaliação da Capes na produção científica dos Programas de Pós-Graduação em Física - Anna Elizabeth Galvao Coutinho Correia (2012)
This thesis is about the relationship between the graduate evaluationpolicies of the Brazilian Educational System and the Brazilian scientificproduction, in physics academic domain, from 2007 until 2009. It aims tostudy the influence of the evaluation policies of Capes, an institution of the Brazilian Government, headed for to support funds to graduate programs and researchers of the academic areas. Its context involved three graduate programs, belonging to federal universities, from Brazilian states named Minas Gerais, Pernambuco and Rio de Janeiro. The assumptions of this research were: the division of the funds for research, the most sensitive part of this system, has been causing serious divergences, because of parameters, used for the analysis of physics graduate programs, that evaluates similarly different knowledge domains, without regard to the peculiarities of each ones. In its theoretical background this thesis discusses: the institutionalization of the science in Brazil, as well as the policies in science and technology, focusing specifically the area of physics; scientific communication and its quality indicators used in the evaluation of academic research, from the point of view of a specific attribute of the science in this thesis named meritocracy. This thesis used quantitative and qualitative methods, such as bibliometrics, scientometrics and content analysis, applied to the researchers scientific production and their interviews results. The analysis categories used were: productivity, incentives, control,and critics to the evaluation system. The research sources used are: 1)Professors, coordinators, and the area of physics Capes representatives; 2) Government documents that stimulate scientific production, such as rules and public notices. The results founded show that: the surveyed institutions has been maintaining instruments of incentive and control to improve scientific production; it has found a predominance of articles that are published in the journals best classified, according to the a classification system used by the sponsoring agency, named Qualis System; the national agency evaluation has been preferring the quantitative methods; that the policies of CAPES pressure researchers to achieve high levels of production, but also causes to them high levels of stress originated from the compulsory obligation of also to develop others administrative and extension activities.